Application of Optical Biosensors in Small-Molecule Screening Activities - Geschwindner, Stefan (Molecular Diversity Preservation International (MDPI), 2012)
The last two decades have seen remarkable progress and improvements in optical biosensor systems such that those are currently seen as an important and value-adding component of modern drug screening activities. In particular the introduction of microplate-based biosensor systems holds the promise to match the required throughput without compromising on data quality thus representing a sought-after complement to traditional fluidic systems. This article aims to highlight the application of the two most prominent optical biosensor technologies, namely surface plasmon resonance (SPR) and optical waveguide grating (OWG), in small-molecule screening and will present, review and discuss the advantages and disadvantages of different assay formats on these platforms. A particular focus will be on the specific advantages of the inhibition in solution assay (ISA) format in contrast to traditional direct binding assays (DBA). Furthermore we will discuss different application areas for both fluidic as well as plate-based biosensor systems by considering the individual strength of the platforms.